Pengaruh Pemberian Edukasi Pra Anestesi Terhadap Tingkat Kecemasan Pada Pasien Laparatomy Dengan General Anestesi - Happy Nurhayati; Nabhani Nabhani; Adinda Thalia Amarra Septa (Lembaga Pengembangan Kinerja Dosen, 2023)
Background Surgical planning for preoperative patients is a psychosocial stressor that can cause stress, anxiety, and depression. Preoperative is the period before surgery is performed, starting from the time the decision is made for surgery until the patient is on the operating table. Laparotomy is one of the major surgical procedures by making an incision in the lining of the abdominal wall to obtain problems in the abdominal organs, such as cancer, bleeding, obstruction, and perforation. Research objectives: The general objective of this study was to determine the effect of implementing education on anxiety levels in preoperative apparatus patients with general anesthesia. Research methodology: This type of research is a quantitative study, with a quasy experimental research plan, with a non-randomized post-test one group design. . Results: It is known that the asymo.sig, (2-tailed) value is 0.000 <0.05. So it can be concluded that the